Development of mathematical learning instruments based on ethnomathematics in character education learning - Ririn Dwi Agustin; Mika Ambarawati; Era Dewi Kartika (Universitas Islam Negeri Maulana Malik Ibrahim, 2018)
The purpose of this research is to develope mathematical learning instrument based on ethnomatematics in strengthening students’ character education. The learning instruments consist of syllabus, lesson plan, and student worksheet. This research is a development study. This research was conducted in grade 8 of junior high school in Indonesia. This research was implemented in three stages, namely: define, design, and develop. The define phase includes the analysis of syllabus, syllabus, lesson plan, and student worksheet; the design stage includes the preparation of learning instruments draft and research instruments; the development stage includes the test of learning instruments, evaluation and perfection of learning instruments. The validation results of expert validators were as follows: syllabus device with a value of 4.62 with a very valid category, student worksheet instruments with a value of 4.59 with a very valid category, while the materials learning device with a value of 3.55 with a very valid category.